Clinical and Biological Determinants of Kidney Outcomes in a Population-Based Cohort Study - Idris Guessous; Belén Ponte; Pedro Marques-Vidal; Fred Paccaud; Jean-Michel Gaspoz; Michel Burnier; Gérard Waeber; Peter Vollenweider; Murielle Bochud (Karger Publishers, 2014)
Background/Aims: Prospective studies on factors associated with adverse kidney outcomes in European general populations are scant. Also, few studies consider the potential confounding effect of baseline kidney function. Methods: We used baseline (2003-2006) and 5-year follow-up data of adults from the general population to evaluate the effect of baseline kidney function and proteinuria on the association of clinical, biological (e.g. uric acid, homocysteine, cytokines), and socioeconomic factors with change in kidney function, rapid decline in kidney function, and incidence of chronic kidney disease (CKD). Estimated glomerular filtration rate (eGFR) and urinary albuminuria-to-creatinine ratio (UACR) were collected. Kidney outcomes were modeled using multivariable regressions. Results: A total of 4,441 subjects were included in the analysis. Among participants without CKD at baseline, 11.4% presented rapid decline in eGFR and/or incident CKD. After adjustment for baseline eGFR and log UACR, only age (Odds Ratio; 1.25 [95%CI 1.18-1.33]), diabetes (OR 1.48 [1.03-2.13]), education (OR middle vs. high 1.51 [1.08-2.11]) and log ultrasensitive CRP (OR 1.16 [1.05-1.22]) were associated with rapid decline in eGFR or incident CKD. Baseline log UACR (OR 1.18 [1.06-1.32]) but not eGFR was associated with rapid decline in eGFR and/or incident CKD. Conclusion: In addition to age and diabetes, education and CRP levels are associated with adverse kidney outcomes independently of baseline kidney function.